Meta-Analysis: Use of Self Talk in Improving Self Efficacy - Sefni Rama Putri (Jurnal SOMASI (Sosial Humaniora Komunikasi), 2021)
The purpose of this study was to analyze the use of self talk on self efficacy. In this study the technique used in the form of meta-analysis by analyzing the data about the effect of self talk on self efficacy. This research begins by formulating research topics, exploring relevant research results for analysis. Data is collected by searching online journals and supporting books. Data were analyzed using quantitative descriptive analysis. Based on the analysis of the use of self-talk can increase self-efficacy from the lowest to the highest.